Fiddling In West Africa: Touching the Spirit in Fulbe, Hausa, and Dagamba Culture.Jacqueline Cogdell DjeDje. 2008. Bloomington: Indiana University Press. 352 pp. - Schauert, Paul (International Library of African Music, 2011)
pages: 247-249
Keywords: African Music